Gramsci: Pedagogy beyond the State - Frosini, Fabio (International Gramsci Journal, 2025)
The concept of pedagogy has a special use in the Prison Notebooks, in that its meaning extends beyond the strictly educational sphere to include the relationship between the State and civil society. All civil society organisations, insofar as they have an organisational function, also have a broadly pedagogical function. In this article, we extend the study of the pedagogical function beyond this parallel between politics and education towards the concept of “personality” on the one hand and the “corporative” structure of society on the other. The concept of personality takes on a relational meaning in the Notebooks. For this reason, it can be said that the organisational and educational activity carried out directly or indirectly by the State must deal with forms of self-education that are always present in society, which in turn are mediated in the corporative structures in society. The conclusion is that to be effective, the pedagogy promoted by politics must go beyond the state and interact with social practices of education and self-education.